The Selection of Aroma-Rich Clones of Vitis vinifera L. cv. Gewtirztraminer and Weisser Riesling by Means of Terpene Analyses - Marais, J.; Rapp, A (South African Journal of Enology and Viticulture, 2017)
Differences in grape aroma between five Gewiirztraminer clones (457/48, 14Gm 035, N20 Kieselberg, 925/643 and FR 46/106) and between fifteen Weisser Riesling clones (239/17Gm, T68, B21, 34, 35, Wl, 110/llGm, N90 Winkel, 813/49, Wl7,37, 24/196Gm, 239, 327 and 198/lOGm) from the Stellenbosch region were investigated over four seasons. Grape samples were analysed for free and bound terpenes. Under the specific conditions of this investigation it was possible to differentiate between some clones of Gewiirztraminer and of Weisser Riesling on the basis of grape-aroma analyses. It, therefore, appears possible to select clones with a higher potential to produce aroma-rich and cultivar-typical wines.